Neutrophils releasing IL-17A into NETs are essential to plasma cell differentiation in inflamed tissue dependent on IL-1R - Lidiane Zito Grund; Ivan Novaski; Valerie F. Quesniaux; Bernhard Ryffel; Monica Lopes-Ferreira; Carla Lima (Taylor & Francis Group, 2017)
Interleukin (IL) 17A in chronic inflammation is also produced by innate immune cells as neutrophils. Mice with chronic humoral response induced by venom of Thalassophryne nattereri (VTn) proved to be a good tool for evaluating the impact of IL-17A on the development of long-lived plasma cells in the inflamed peritoneal cavity. Here, we report that VTn induces IL-17A production by neutrophils accumulating in the peritoneal cavity and triggers the extrusion of IL-17A along with neutrophil extracellular traps (NETs). Neutrophil depletion reduced the number of IL17A-producing cells in VTn-immunized mice and blocked the differentiation of long-lived plasma cells. Specific antibody production and survival of long-lived plasma cells was ablated in VTn-immunized mice deficient in CD4, while CD28 signaling had the opposite effect on differentiation of long-lived plasma cells. Further, maturation of long-lived plasma cells in inflamed peritoneal cavity was IL-1R1 and COX-2 dependent. Finally, when both the Raf-MEK-ERK pathway and the IL-17A or IL-1R1 activities were blocked, neutrophils were unable to promote the differentiation of memory B cells into long-lived plasma cells, confirming the essential role of neutrophils and IL-17A along with NETs in an IL-1/IL-1R-dependent manner as the novel helping partner for plasma cell differentiation in chronically inflamed tissues.